ANALISA BAKTERI TAHAN ASAM PADA DAHAK PEROKOK AKTIF PENDERITA TUBERKULOSIS PARU - Sinaga, Eka Margaretha; Siahaan, Maniur A; Sipayung, Apriska Dewi (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Acid fast bacteria (AFB) are cell walls containing complex lipids so that in Ziehl-Neelsen staining they can bind dyes because they are not washed off by 3% HCl Alcohol (Alcoholic Acid). One of the host factors in pulmonary tuberculosis is smoking habits and exposure. Smoking habits will damage the defense mechanism of the lungs, which causes the lungs to be more easily infected with tuberculosis germs. The purpose of this study was to determine the results of analysis of acid-fast bacteria in the sputum of active smokers. The research method used was descriptive cross-sectional by examining acid-fast bacteria in the sputum of active smokers suspected of having pulmonary tuberculosis by microscopic examination of sputum (direct smear smear) using the Ziehl-Neelsen staining method. smear examination with Ziehl-Neelsen staining in patients with tuberculosis at Putri Hijau Hospital in 2022, totaling 20 samples, found 4 positive results and 16 samples with negative results.